Psychometric Evaluation of the Good Death Index from Patients with Terminal Cancer’s Perspectives: A Mixed-Methods Study - Pi SH; Li IF; Li PY; Lai YL; Fang CK (Journal of Multidisciplinary Healthcare)
Shih-Hsuan Pi,1– 3 In-Fun Li,4,5 Pei-Yi Li,6 Yuen-Liang Lai,7 Chun-Kai Fang6– 9 1Department of Medical Research, Tamsui Branch, MacKay Memorial Hospital, New Taipei, Taiwan; 2General Education Center, MacKay Junior College of Medicine, Nursing, and Management, New, Taipei, Taiwan; 3Department of Crime Prevention, Central Police University, Taoyuan, 33304, Taiwan; 4Center of Long-Term Care, Tamsui Branch, MacKay Memorial Hospital, New Taipei, Taiwan; 5Department of Nursing, MacKay Medical College, New, Taipei, Taiwan; 6Department of Thanatology and Health Counseling, National Taipei University of Nursing and Health Sciences, Taipei, Taiwan; 7Hospice and Palliative Care Center, Tamsui Branch, MacKay Memorial Hospital, New Taipei, Taiwan; 8Department of Death Care Service, MacKay Junior College of Medicine, Nursing, and Management, New Taipei, Taiwan; 9Department of Psychiatry, MacKay Memorial Hospital, New Taipei, TaiwanCorrespondence: Chun-Kai Fang, Hospice and Palliative Care Center, MacKay Memorial Hospital Tamsui Branch, New Taipei, Taiwan, Email chunkai.fang0415@gmail.comBackground: Patients with terminal illness often experience significant physical and mental suffering. This distress affects the patients themselves, as they endure the pain of their condition and their family members, who are affected by the patient’s situation and medical decisions. Furthermore, exploring the patients’ and their families’ concepts of a “good death” is crucial for reflecting on the value of life and for planning treatment or care models (such as advance care planning). Therefore, understanding the issues is essential in improving palliative care and the overall quality of life.Aim: This study aimed to develop a clinical assessment tool for the self-assessment of patients with terminal cancer to determine whether they are approaching a good death.Methods: Our good death concept was developed through in-depth interviews with terminal cancer patients and qualitative analysis by experts in a research program. Three themes were analyzed: “living in dying (L)”, “experiencing the existential self (E)”, and “dying in living (D).” Therefore, the principal and co-principal investigators designed the primary LED Good Death Index (LED-GDI) based on three major themes and 15 subtopics of the LED Good Death concept.Results: A total of 144 participants completed the LED-GDI assessment. Cronbach’s alpha for the LED-GDI was 0.854. We found that the LED-GDI allowed patients to assess whether they were approaching a good death.Conclusion: The philosophical concept of LED-GDI is particularly in line with Confucian culture in East Asia and emphasizes the importance of living well before death. Therefore, the most critical goal of clinical end-of-life care is to determine whether patients with terminal illness can achieve a good death and live until the last moment.Keywords: attitude to death, existentialism, good death index, end-of-life care